Safety and feasibility of performing robotic ureteroureterostomy and robotic pyeloplasty in infants - Suarez Arbelaez, Maria Camila; Ghattas, Yasmine; Raymo, Adele; Isern, Samantha; Alam, Alireza; Nassau, Daniel E.; Castellan, Miguel (Frontiers in Urology, 2022)
Introduction: Open surgery is considered the standard of care for pediatric urological procedures. Nonetheless, Robotic Assisted Laparoscopic Surgeries (RALS) have become increasingly popular in pediatrics as they allow for quicker recovery times, lower narcotic use, better cosmesis, and better intraoperative visibility. However, there are concerns regarding the usefulness of RALS in the infant population, as operating on smaller patients limits mobility of the robotic arms and can result in arm collisions. Objective: The aim of this study was to compare the clinical and postoperative outcomes of infants undergoing robotic vs open pyeloplasty or ureteroureterostomy. Materials and Methods: Retrospective study conducted between 2012 to 2022, 114 infants who underwent pyeloplasty (81 open pyeloplasty and 33 robotic pyeloplasty) and 21 who underwent ureteroureterostomy (9 open ureteroureterostomy and 12 robotic ureteroureterostomy) were included. Results: Mean age at surgery in the pyeloplasty cohort was 4.81 ± 3.1 months in the open group, and 6.24 ± 2.6 months in the robotic group (p=0.13), and in the ureteroureterostomy cohort was 7.67 ± 3.16 months in the open group and 7.58 ± 2.75 months in the robotic group (p=0.95). Operative time was found to be shorter in robotic pyeloplasty and robotic ureteroureterostomy, when compared to the open approaches. Postoperative complications, its severity, and the surgical success were comparable among the pyeloplasty and ureteroureterostomy groups. Only 1(3%) complication related to the robotic technique was reported in the pyeloplasty cohort. The length of hospital stay was found to be similar between the ureteroureterostomy groups, while in the pyeloplasty cohort the robotic group showed a significant shorter hospital stay than the open group. Overall, the mean follow-up was greater than 12 months. Conclusion: Our results demonstrated that robotic pyeloplasty and ureteroureterostomy performed in infants are feasible, safe, and durable procedures, with an additional benefit of reducing duration of operative time and hospital stay.